2017
DOI: 10.14701/ahbps.2017.21.3.107
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and post-resection outcomes of biliary cystadenoma and cystadenocarcinoma of the liver

Abstract: Backgrounds/AimsBiliary cystadenoma (BCA) and biliary cystadenocarcinoma (BCAC) account for 5%-10% of liver cystic diseases. In this study, we analysed the clinical presentation and surgical management of patients with BCA and BCAC.MethodsWe retrospectively analysed the medical records of 23 BCA and 7 BCAC cases diagnosed between January 2007 and December 2013.ResultsThere was a statistically significant difference in age (p=0.044) and sex (p=0.048) between BCA and BCAC groups. In the BCA group, 17 patients sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
2
18
0
5
Order By: Relevance
“…A retrospective study conducted by Jwa et al . in South Korea showed that in patients undergoing complete resection there was no tumor recurrence in patients with BCA and in patients with BCAC, 1-, 3- and 5-year disease-free and overall patient survival rates were 100%, 85.7%, 57.1%, and 100%, 100%, 75.0% respectively [ 34 ].…”
Section: Biliary Cystadenocarcinomamentioning
confidence: 99%
“…A retrospective study conducted by Jwa et al . in South Korea showed that in patients undergoing complete resection there was no tumor recurrence in patients with BCA and in patients with BCAC, 1-, 3- and 5-year disease-free and overall patient survival rates were 100%, 85.7%, 57.1%, and 100%, 100%, 75.0% respectively [ 34 ].…”
Section: Biliary Cystadenocarcinomamentioning
confidence: 99%
“…10 The current literature suggests that cystadenocarcinomas have a fairly favorable prognosis if completely resected. 10,11 However, one series suggests that an anaplastic alteration is a sign of impending aggressive invasion by the tumor. 9 In that series, all 3 patients with an anaplastic component died of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…MCN-L has previously been known as biliary cystadenoma or cystadenocarcinoma [ 3 ]. We have previously reported 23 cases of biliary cystadenoma and seven cases of biliary cystadenocarcinoma [ 9 ], for which the definition of MCN-L according to the WHO 2010 classification was not adopted because these study patients had undergone surgical resection between 2007 and 2013.…”
Section: Introductionmentioning
confidence: 99%